The 2012–2016 eruptive cycle at Copahue volcano (Argentina) versus the peripheral gas manifestations: hints from the chemical and isotopic features of fumarolic fluids - Tassi, Franco (2017)
Fil: Tassi, F. Department of Earth Sciences, University of Florence, Institute of Geosciences and Earth Resources of the National Research Council. Florencia; Italia.